Multi‐functional hybrid active power converter and its industrial application for electrolytic copper‐foil. Issue 16 (1st December 2016) - He, Zhixing; Ma, Fujun; Li, Mingshen; Xu, Qianming; Zhou, Fayun; Yue, Yufei
Abstract : To meet the requirements of high‐power compensating occasion such as electrochemical industries, a multifunctional hybrid active power converter (HAPC) with LC series filter is studied to effectively integrate functions of rectification and power compensation. HAPC can be used as a high‐power pulse width modulation rectifier to supply its dc load, meanwhile, it can also compensate large amount of reactive and harmonic current without increasing the voltage rating of itself. A compound current control method for HAPC is introduced so as to improve the dynamic tracking performance. The current and voltage dual closed‐loop system of HAPC is built in s domain, and the detailed control parameters are designed to tune control performance further. Finally, a set of 800 kVA HAPC system for electrolytic copper‐foil is developed. The results show that the HAPC system can achieve expected operation performance and largely improves power quality of power grid.